2022
DOI: 10.1039/d2bm00221c
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal-enhanced antibacterial and antioxidant hydrogel dressings based on catechol-modified chitosan-derived carbonized polymer dots for effective treatment of wound infections

Abstract: Bacterial infection and excess reactive oxygen species (ROS) remain challenging factors contributing for the delayed healing of chronic wounds. Although various antibacterial and antioxidant hydrogel dressings have been developed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Our group prepared carbonized polymeric dots (CPDs) 70 with photothermal enhanced antibacterial effects by using catechol-modified chitosan polymer as the precursor (Fig. 5).…”
Section: Photothermal Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group prepared carbonized polymeric dots (CPDs) 70 with photothermal enhanced antibacterial effects by using catechol-modified chitosan polymer as the precursor (Fig. 5).…”
Section: Photothermal Effectmentioning
confidence: 99%
“…The authors investigated the binding interactions of CDs on DNA and RNA in bacteria by dynamic light scattering (DLS), circular dichroism spectroscopy and gel electrophoresis. The results showed that CDs can bind 70 to DNA and RNA and fungi through non-covalent bonds, change the secondary structure of DNA and RNA, and then affect the genetic processes of bacteria and fungi, ultimately killing them. Hao et al prepared PC-CQDs that were able to disrupt the membrane structure of bacteria by physical action and cause cytoplasmic exocytosis.…”
Section: Affecting Bacterial Cellular Life Activitiesmentioning
confidence: 99%
“…In addition, PVA@CPD hydrogels can act as effective antioxidants to scavenge free radicals while possessing broad-spectrum and rapid bactericidal activity. [106] In addition, by compounding with other hydrogel matrices, PVA-based hydrogels can be endowed with hemostatic, anti-inflammatory, antibacterial, or other functions that are beneficial to wound healing. Qing et al designed a multifunctional hydrogel with synergistic photothermal antibacterial activity and enhanced bone regeneration by adding MgO NPs and BP NSs to a PVA/CS matrix.…”
Section: Synthetic Hydrogelmentioning
confidence: 99%
“…Nano-materials such as silver nanoparticles (NPs), zinc oxide (ZnO) NPs, titanium dioxide NPs, antimicrobial peptides, aggregation-induced emission materials, graphene oxide, carbon nanotube, polymer NPs, carbon dots (CDs), and some carbonized nanomaterials offer a multitude of opportunities to inhibit or kill pathogenic microorganisms. [12,[16][17][18][19][20][21][22][23][24][25][26][27] Among them, as a zerodimensional carbon material consisting of a conjugated core and surface functional groups, CDs have attracted extensive interest due to their outstanding features. Since discovered in 2004, [32] Copyright 2021, Elsevier.…”
Section: Introductionmentioning
confidence: 99%